Analisis Implementasi Pengawasan Ketertiban Ground Support Equipment (GSE) oleh Unit Apron Movement Control (AMC) di Sisi Udara Bandar Udara Mopah Merauke - Uswatun, Mega; Widagdo, Djoko (As-Syirkah: Islamic Economic & Financial Journal, 2024)
AMC unit supervision of GSE order is a very important thing to do to maintain security and safety in the airside area, considering that there are still many violations that still occur in the airside area of ​​Mopah Merauke Airport. The aim of this research is to find out how the AMC unit implements monitoring of GSE order on the air side and to find out what obstacles there are and what efforts are made by the AMC unit in monitoring GSE order on the air side of Mopah Merauke Airport. When the author does research, they utilize a descriptive method with a qualitative approach, gathering data through participant observation, structured interviews, and documentation gathered from pertinent sources. The results of this research indicate that 1) AMC unit supervision has not been optimal in carrying out supervision of GSE order. 2) AMC officers have obstacles in monitoring GSE order because they have limited human resources and technology to carry out effective supervision of all GSE activities and lack of awareness and compliance of GSE users. against the procedures that have been established 3) the efforts made by the AMC unit in monitoring GSE order and taking action against officers who commit violations.